Applied social sciences social Work - Runcan, Patricia-Luciana; Rata, Georgeta; Cojocaru, Stefan (Cambridge Scholars Publishing, 2013)
This book, Applied Social Sciences: Social Work, is a collection of essays specific to the field of social work. The approach is both holistic (assessment of social work, burnout, counselling, history of social work, migration, models of excellence in social work, unemployment, workaholism) and atomistic (child attachment, children's rights, coping strategies and associated work - family conflict, emotional neglect, monoparental families, physical abuse, positive child disciplining, psycholog...
Keywords: Social service; Human services